Effective strategies for optimizing rapeseed cultivation involve the careful selection of varieties and the appropriate use of pesticides - Pant, Janak; Dawadi, Prava (International Journal of Sustainable Agricultural Research, 2024)
This research investigates the management of rapeseed through suitable application of pesticides and variety selection. Control of aphid and variety selection of mustard have some detrimental effects on crop growth, development, and yield. Therefore, from November 2017 to February 2018, we conducted an experiment to assess the status of mustard using various varieties and pesticides. The experiment was laid out in split-plot design with three replications. The three varieties (Pragati, Bikash, Unnati) of mustard are the main factor, and insecticidal and treatment were subfactors of experiment, which included Spinosad 45% suspension concentrates at 0.44 ml/liter water, Imidacloprid 70 water dispersible granule at 14 gm/ liter water, Beauveria bassiana 1.15% wettable powder at 2g/liter water, and untreated control. Phenological characters for plant variety were assessed to record the data regularly. Bikash had the higher plant height among other varieties. Higher leaf and branch numbers, including number of seeds per pod, were to be found the highest in the variety Pragati, but yield, biomass, and harvest index were statistically similar in all varieties. Seeds per pod, yield, biomass, and harvest index were the highest with Imidacloprid, followed by Beauveria, Spinosad, and Control. The highest number of aphid populations was seen during the last week of December-mid-January. Imidacloprid was found to be the most effective and economically viable option for rapeseed growth and production. Similar effects from cropping any varieties, Unnati, and Bikash Pragati were noticed.